2020
DOI: 10.3171/2020.7.focus20426
|View full text |Cite
|
Sign up to set email alerts
|

The role of frailty in geriatric cranial neurosurgery for primary central nervous system neoplasms

Abstract: OBJECTIVEFrailty is a clinical state of increased vulnerability due to age-associated decline and has been well established as a perioperative risk factor. Geriatric patients have a higher risk of frailty, higher incidence of brain cancer, and increased postoperative complication rates compared to nongeriatric patients. Yet, literature describing the effects of frailty on short- and long-term complications in geriatric patients is limited. In this study, the authors evaluate the effects of frailty in geriatric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
35
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 36 publications
0
35
0
1
Order By: Relevance
“…The present study confirms that surgical resection of BT in patients older than 65 is feasible and rather safe [ 5 , 7 , 26 ]. The recently growing interest in elderly neuro-oncological patients has generated a series of studies that highlight how increased age (≥65 years), alone does not represent an independent risk factor associated with worse outcomes [ 27 ]. It has been demonstrated that frailty, described as the “clinically recognizable state of increased vulnerability resulting from age-associated physiological decline” [ 27 ], is per se an outcome predictor, but not the only one.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The present study confirms that surgical resection of BT in patients older than 65 is feasible and rather safe [ 5 , 7 , 26 ]. The recently growing interest in elderly neuro-oncological patients has generated a series of studies that highlight how increased age (≥65 years), alone does not represent an independent risk factor associated with worse outcomes [ 27 ]. It has been demonstrated that frailty, described as the “clinically recognizable state of increased vulnerability resulting from age-associated physiological decline” [ 27 ], is per se an outcome predictor, but not the only one.…”
Section: Discussionmentioning
confidence: 99%
“…These data confirm those of Maldaner et al [ 7 ], in particular, a higher rate of perioperative complications in elderly patients. Shahrestani et al recently highlighted that the complication rate significantly differs between frail and non-frail elderly patients immediately following cranial surgery [ 27 ]. In contrast, they also suggest that there may be no significant difference in long-term follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations